The role of islamic religious education teachers in sex education for visually impaired children at slb negeri temanggung - Ikhsanu Yusron; Ananda Abro Wiant; Luluk Ifadah; Ana Sofiyatul Azizah; Syalma Indah Fitrianti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to examine the role of Islamic Education teachers in delivering sex education to visually impaired students at SLB Negeri Temanggung, and to explore the instructional methods employed to support students’ understanding of sexuality in a contextual and Islamic framework. The background of this research stems from the lack of sex education among children with special needs, particularly the visually impaired, who are more vulnerable to sexual violence due to visual limitations and low sexual literacy. This study employs a phenomenological approach to understand the experiences and meanings of the role of teachers in sex education for visually impaired students. The type of research used is field research, as it is conducted directly at the location where the subjects are situated. The qualitative method is applied, with data collection techniques including observation, interviews, and documentation. The data sources consist of primary data, namely Islamic Religious Education teachers, and secondary data in the form of books, journals, and school documents. Data analysis is carried out through data reduction, data presentation, and conclusion drawing. To ensure data validity, triangulation is applied in three forms source, technique, and time. The results indicate that role of Islamic Education teachers play multiple roles as educators, mentors, and motivators in delivering sex education. The dominant teaching methods used are lectures and question-answer sessions, supported by audio media. This strategy is deemed effective as it aligns with the sensory conditions of visually impaired students who rely heavily on hearing for understanding. Teachers also successfully create a safe and open learning environment, encouraging students to discuss sensitive topics confidently. This study concludes that the active involvement of Islamic Education teachers in value-based sex education is crucial in equipping visually impaired students with the knowledge, skills, and attitudes needed to protect themselves from deviant behavior and sexual abuse